Compensation for Consumers for Illegal Acts in E-Commerce Transactions from the Perspective of Legislation - Muskibah Muskibah; Diana Amir; Lili Naili Hidayah; Pahlefi Pahlefi; Suhermi Suhermi (Al-Makki Publisher, 2026)
The rapid growth of e-commerce has significantly reshaped the global marketplace, enabling consumers to engage in digital transactions easily. However, alongside its benefits, e-commerce has introduced challenges, particularly regarding consumer protection in cases of unlawful acts committed by business actors. The aim of this study is to analyze the legal concept of compensation for consumers in e-commerce transactions, focusing on unlawful acts. This research investigates the responsibilities of business actors in ensuring consumer protection and the applicability of various laws, such as the Civil Code, the Consumer Protection Law, and the Electronic Information and Transaction Law (ITE Law), to e-commerce contexts. Using a descriptive-analytical approach with normative juridical methods, the research explores case law, legal frameworks, and secondary data related to consumer complaints, including issues of fraud, product misrepresentation, and privacy violations. The findings highlight the complexities surrounding compensation claims for both material and immaterial damages resulting from e-commerce violations. The study concludes that there is a need for stronger legal provisions to ensure fair compensation and accountability for e-commerce business actors. This research also recommends enhancing digital literacy among consumers and reinforcing the regulatory mechanisms to promote a safer e-commerce environment. The study contributes to a deeper understanding of consumer rights in the digital economy and suggests improvements in the legal framework for e-commerce transactions.